Pengaruh Waktu Tahan Dan Penambahan Kadar Garam Dapur (NaCl) Dalam Media Pendingin Air Pada Proses Hardening Terhadap Sifat Mekanik Dan Struktur Mikro Baja Karbon Rendah - Suriady Sihombing; Charles Manurung; Jonner Togatorop; Richard A M Napitupulu (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2019)
This study aims to determine the effect of salt (NaCl) in water cooling media with different levels of 10%, 16% and 25% against the hardness level of low carbon steel tested with Vickers after hardening in the hardening process and to determine the proportion of media which coolant produces the highest hardness from the use of water cooling media which is added to different levels of NaCl. The independent variable in this study is the amount of salt (NaCl) dissolved in water cooling media with different percentages, namely 10%, 16% and 25%. While the dependent variable is the value of the hardness of the material tested with Vickers. Hardness in the hardening process with water cooling media which added different salt (NaCl), 10%, 16% and 25% is 185.02 VHN, 229 VHN and 284 VHN. From the results of the study it was found that there was an effect of the salt content (NaCl) in the water cooling media on the level of hardness in the hardening process of low carbon steel. Higher level of salt will increase value of hardness. The highest hardness was achieved in cooling media with a concentration of 25% NaCl that is equal to 284 VHN followed by cooling media with a concentration of 16% NaCl of 229 VHN and the lowest was a cooling medium with a concentration of 10% NaCl of 185.02 VHN.